2013 35th Annual International Conference of the IEEE Engineering in Medicine and Biology Society (EMBC) 2013
DOI: 10.1109/embc.2013.6610563
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the anisotropic mechanical properties of the skull in low-intensity focused ultrasound towards neuromodulation of the brain

Abstract: Lately, neuromodulation of the brain is considered one of the promising applications of ultrasound technology in which low-intensity focused ultrasound (LIFU) is used noninvasively to excite or inhibit neuronal activity. In LIFU, one of critical barriers in the propagation of ultrasound wave is the skull, which is known to be highly anisotropic mechanically: this affects the ultrasound focusing, thereby neuromodulation effects. This study aims to investigate the influence of the anisotropic properties of the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2015
2015

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…More realistic models have led to better approximation of focal pressure and size [25], and animal work has demonstrated that FUS can have excellent targeting. For example, focused ultrasound in rats caused increase in glucose metabolism with high spatial specificity [6].…”
Section: Refining Parameters and Expanding Applicationsmentioning
confidence: 99%
“…More realistic models have led to better approximation of focal pressure and size [25], and animal work has demonstrated that FUS can have excellent targeting. For example, focused ultrasound in rats caused increase in glucose metabolism with high spatial specificity [6].…”
Section: Refining Parameters and Expanding Applicationsmentioning
confidence: 99%